Effect of polyphenol and pH on cocoa Maillard-related flavour precursors in a lipidic model system. - S.S., Noor Soffalina; Selamat, Jinap; Saari, Nazamid; Sheikh Abdul Hamid, Nazimah (Wiley-Blackwell, 2009)
Polyphenol and pH influence the flavour quality of cocoa beans during roasting. Amino acids and reducing sugars are flavour precursors in cocoa beans, which develop into cocoa-specific aroma through Maillard reactions during roasting. A central composite design was applied to determine the combined effect of polyphenol and pH on the flavour precursors during cocoa roasting at 120 °C for 45 min using a lipidic model system. Polyphenol was added at 40, 80 and 120 g kg−1 and pH was adjusted to 4.5, 6 and 7.5. The response surface methodology revealed that a lower concentration of amino acids and reducing sugars was obtained at higher polyphenol concentration (120 g kg−1) and lower pH value (4.5). Based on the constraints set, the best polyphenol concentration of 43–58 g kg−1 and pH of 7.0–7.5 was found to be optimum for the formation of flavour precursors in this lipidic model study.